Profile of Febrile Seizures in Pediatric Patients at Dr. Adnaan WD Payakumbuh Hospital 2019 - Nadia Purnama Dewi; febianne eldrian; Ovi OKtavian (Faculty of Medicine, Universitas Andalas, 2022)
Background: Febrile seizures are seizures between the ages of 6 and 60 months with a temperature of 38℃ or higher that are not the result of central nervous system infection or any metabolic imbalance and that occur in the absence of a history of prior afebrile seizures. Purpose: Know the profile of fever seizures of pediatric patients at Dr.Adnaan WD Payakumbuh Hospital in 2019. Method: This research is retrospective descriptive with a cross-sectional approach. The sample is all pediatric patients who had seizures in 2019 with 91 samples. Data were analyzed univariately and presented in frequency distribution and percentage. Result: Based on the study results, in children who have seizures fever, most are men, with the age of 12 months. Most febrile seizures occurred at a temperature of 39.1℃. The average blood leukocyte level of a child with a fever seizure is 13,997.80 mm³. Conclusion: The most age is 12 months, the most sex is male, the average body temperature of children who have febrile seizures is 39.1 °C, and the intermediate blood leukocyte level of children who have febrile seizures is 13,886.60 mm³.